Wireless Network Service Quality Analysis at Kefamenanu 1 State Vocational School using QoS Methods - Silla , Intan Nubriyanti; Rema, Yasinta Oktaviana Legu; Fallo, Kristoforus (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Indonesia is one of the largest archipelagic countries in the world, one of the challenges is that the existing internet network is not optimal and should be evenly distributed throughout Indonesia. This article is one of the efforts to increase the capacity and use of the internet, especially to support the education process which should be evenly distributed in various regions in Indonesia, not only in Java but also in areas outside Java. especially in East Nusa Tenggara. NTT is one of the areas discussed in this article, specifically at Kefamenanu 1 State Vocational School. This article puts forward some essential aspects in the development and installation of the internet in this school, including using the right measurements of Quality of Service (QoS). QoS includes many things such as Throughput, Bandwidth, Packet Loss, and other parameters that are essential in building and analyzing internet networks that have a wide scope, especially for the Education level. Vocational High Schools are not only expected to be able to use the internet but also build, design, install, and perform detailed analysis on the internet network they build. Two essential networks must be able to be installed, i.e., a Wireless Network and Local Area Network.